GPS ソウタイ ソクイ ニ ヨル サイキン ノ ヒガシ ナンキョク ヒョウショウ ノ シラセ リュウイキ オヨビ ドームフジ シュウヘン ノ ヒョウショウ リュウドウ カンソク - 本山, 秀明; モトヤマ, ヒデアキ; 古川, 晶雄; フルカワ, テルオ; 西尾, 文彦; ニシオ, フミヒコ; Motoyama, Hideaki; Furukawa, Teruo; Nishio, Fumihiko (2008)
P(論文) 1992年から氷床流動観測を目的としたGPS (Global Positioning System: 全地球測位システム)観測が開始された.最初は沿岸からドームふじ基地へのトラバースルート沿いに設けた11地点を基本観測点として,内陸旅行中に適宜GPS観測を行った.その後,白瀬流域の主流線沿いと等高線沿い,ドームふじ基地南方へと観測地域を拡大した.氷床流動に関しては,白瀬流域の下流ほど氷床流動速度が大きい.また白瀬流域において,従来から観測されている氷床表面の低下が確認され,この低下速度は0.1-0.2m/年であった. Surface ice sheet flow velocity has been observed using the differential GPS (Global Positioning System) method since 1992. The basic GPS stations along traverse routes from S16 to Dome Fuji were set up at 11 sites and the GPS observations were performed during inland traverse expeditions. After that, the observational area was expanded along contour lines and the main stream line in the Shirase drainage basin to the south of Dome Fuji Station. The flow velocities at GPS stations are reported. The thinning of the ice sheet surface reported from the past was observed in Mizuho Glacier basin. The thinning rates were 0.1-0.2m/year. departmental bulletin paper